STUDY OF THE IMPLEMENTATION OF THE DUALISM OF THE AL AZHAR CURRICULUM AND THE 2013 CURRICULUM IN FIQH LESSONS AT MADRASAH ALIYAH AL ITTIFAQIAH - Meriyanti, Meriyanti; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhammad; Adi Fernando, Derri (Conciencia, 2024)
This research aims to analyse the design of the Al Azhar curriculum and the 2013 curriculum in learning Fiqh subjects and the strategy for implementing the dualism of the Al Azhar curriculum and the 2013 curriculum in learning Fiqh subjects at Madrasah Aliyah Al Ittifaqiah. The approach in this research uses qualitative descriptive research with the type of field research, collecting data in the field, namely to observe the phenomena that will be researched in the field, using interviews, observation and documentation data collection techniques, sourced from stakeholders, Fiqh teachers and al Azhar students at MA Al Ittifaqiah, as for the data analysis technique, the researcher analysed the data using the Miles and Huberman analysis model. The results of this research show that the design of the Al Azhar curriculum and the 2013 curriculum uses a subject centered design pattern with the subject design and discipline design categories, and learn centered design with variations in the activity or experience design model, as well as problem centered design with model variations. the areas of living design. The teacher's strategy in implementing dualism curriculum is, in the Al Azhar curriculum the teacher uses active learning strategies and expository strategies with sorogan, lecture, story and question and answer methods, and Madrasah Fiqh (K-13) learning strategies, teachers use problem-based learning strategies, contextual teaching, expository and cooperative learning, using discussion, lecture, question and answer and story methods.